2014
DOI: 10.1111/imj.12329
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Erdheim–Chester disease with combination of interleukin‐1‐targeting drugs and high‐dose glucocorticoids

Abstract: Erdheim-Chester disease (ECD) is a rare histocytic disorder. We report a case of a 45-year-old male ECD patient with severe clinical manifestation (urinary obstruction due to retroperitoneal mass with hydronephrosis, involvement of long bones) and central nervous system involvement (hemiparesis, aphasia and diabetes insipidus). Diagnosis was confirmed by typical clinical, radiological and histological findings. Under immunosuppressive therapy with prednisolone and interleukin-1A receptor antagonist (Anakinra, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The efficacy of anakinra SD treatment appeared variable; both efficacy and failure are reported in sparse cases of cardiac, neurological and pleural ECD involvements. 7,9,20 The variability of the anakinra response in ECD should depend on the organ involved and might be related to at least two phenomena. First, beside the blockade of the inflammatory paracrine action of circulating IL-1b, the efficacy of anakinra in ECD is also probably related to the blockade of juxtacrine, i.e., direct intercellular contact and interactions between pathologic histiocytic cells via membranous IL-1a overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of anakinra SD treatment appeared variable; both efficacy and failure are reported in sparse cases of cardiac, neurological and pleural ECD involvements. 7,9,20 The variability of the anakinra response in ECD should depend on the organ involved and might be related to at least two phenomena. First, beside the blockade of the inflammatory paracrine action of circulating IL-1b, the efficacy of anakinra in ECD is also probably related to the blockade of juxtacrine, i.e., direct intercellular contact and interactions between pathologic histiocytic cells via membranous IL-1a overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…However, further cases of complete response (CR) and partial response (PR) or failure are observed with this posology in ECD. [6][7][8][9][10][11] Tocilizumab, a monoclonal antibody blocking the IL-6 receptor, has also been tried with success in a few patients. 12 More recently, treatments targeting the RAS/RAF/MEK/ERK tumourigenic mutational network provided several cases of dramatic CR in ECD.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other non-surgical treatments currently being investigated for ECD patients with a more disseminated disease including: methotrexate 18 , canakinumab 19 , vemurafenib (20), and interleukin-1 targeting drugs/ glucocorticoids. 21 Vemurafenib, a BRAF inhibitor, has recently been utilized as an effective treatment for ECD patients harboring the BRAFV600E mutation with severe and refractory ECD, resulting in significant clinical improvement. 2,7 of infiltrating foamy, lipid-laden histiocytes, characteristic multinucleated Touton-type giant cells, and fibrosis.…”
Section: General Neurosurgerymentioning
confidence: 99%
“…1 Several reports have suggested that an interleukin (IL)1 receptor antagonist, anakinra, is effective in treating ECD. [2][3][4][5][6][7][8] Twelve patients (7 men and 5 women; median age, 70 years; range, 22-80 years) with biopsy-proven ECD 9 and previous failure (cases 2, 3, 4, 9, and 11), poor tolerance, or contraindication (cases 1, 2, 5, 6, 7, 8, 10, and 12) to interferon-a (IFN-a) therapy received alternative treatment with daily subcutaneous injection of 100 mg anakinra. Data collection and analysis were performed retrospectively.…”
mentioning
confidence: 99%
“…Since then, the use of IL-1 blockade in ECD has been reported in 6 additional reports [3][4][5][6][7][8] (Table 2), which did not mention any changes in bone lesions or retroperitoneal infiltration. Killu et al 5 described a patient with a right atrial mass in which FDG uptake decreased under anakinra treatment, although there was no MRI evaluation of the cardiac infiltration.…”
mentioning
confidence: 99%